Greater severity and extent of periodontal breakdown in 136 south Indian human immunodeficiency virus seropositive patients than in normal controls: A comparative study using community periodontal index of treatment needs - Ranganathan K; Magesh K; Kumarasamy N; Solomon Suniti; Viswanathan R; Johnson Newell (Wolters Kluwer Medknow Publications, 2007)
Apart from the more or less distinctive forms of periodontal disease associated with human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome there remains considerable uncertainty as to whether or not conventional destructive periodontitis is exacerbated in HIV positive individuals. This is especially so in developing countries, from which few studies have been reported. The present study compared the severity and extent of periodontal breakdown in 136 HIV positive individuals from Chennai, South India, with 136 age-matched controls from the same low socio-economic and ethnic group. All surfaces of all teeth were scored for the community periodontal index of treatment needs (CPITN). Statistical analysis was performed using SPSSTM package. The results of the present study show that CPITN is a simple, useful technique to assess periodontal status in immunosuppressed patients and that periodontitis is associated with immunosuppression and oral candidiasis. The assessment of periodontal status could thus be a useful tool in minimally invasive screening of populations for HIV disease, especially in those parts of the world, like India and Africa, with high prevalence and rising incidence.